The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1074/jbc.274.52.37335
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Fatty Acid Regulation of the Human Δ-5 Desaturase

Abstract: Arachidonic (20:4(n-6)), eicosapentaenoic (20:5(n-3)), and docosahexaenoic (22:6(n-3)) acids are major components of brain and retina phospholipids, substrates for eicosanoid production, and regulators of nuclear transcription factors. One of the two rate-limiting steps in the production of these polyenoic fatty acids is the desaturation of 20:3(n-6) and 20:4(n-3) by ⌬-5 desaturase. This report describes the cloning and expression of the human ⌬-5 desaturase, and it compares the structural characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
380
4
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(399 citation statements)
references
References 40 publications
13
380
4
2
Order By: Relevance
“…Examples of the blots are given in Figure 1. The sizes of the immunoreactive bands for both enzymes were approximately 50 kDa, which is consistent with the molecular weights of D5d and D6d proteins reported in other species (Cho et al, 1999a and1999b). Across diets, the average expression of D5d protein was the highest in muscle, followed by subcutaneous adipose tissue, with the lowest level in the liver (Table 6).…”
Section: Pig Maternal Diet Fatty Acids Enzyme Expressionsupporting
confidence: 85%
“…Examples of the blots are given in Figure 1. The sizes of the immunoreactive bands for both enzymes were approximately 50 kDa, which is consistent with the molecular weights of D5d and D6d proteins reported in other species (Cho et al, 1999a and1999b). Across diets, the average expression of D5d protein was the highest in muscle, followed by subcutaneous adipose tissue, with the lowest level in the liver (Table 6).…”
Section: Pig Maternal Diet Fatty Acids Enzyme Expressionsupporting
confidence: 85%
“…It has been suggested that this inhibitory effect of carbohydrates on SCD1 mRNA abundance in the liver can be mediated by hormonal factors, such as leptinaemia (Lengi and Corl, 2007;Bernard et al, 2012), but no difference in the concentration of plasma leptin between the two experimental groups was observed in our study. On the other hand, the reduction in the mRNA abundance of FADS2 in the liver of goats fed the SFO diet, most likely caused by a negative effect of n-3 PUFA on the expression of this gene (Cho et al, 1999), might explain the decrease in the 18:3n-6 and 20:3n-6 concentrations in the liver, which could also be related to the lower supply of their precursor, 18:2n-6, in the SFO diet. In contrast, the different dietary treatments did not lead to changes in the mRNA abundance of the transcription factors regulating lipogenic gene expression (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, desaturase assays are routinely designed after fasting [15] because high variability in desaturase activities comes from the nutritional status of the animals. While dietary PUFA are known to suppress the expression and activity of ∆6-and ∆5-desaturases [23,24], the effect of individual saturated FA has been less explored.…”
Section: Discussionmentioning
confidence: 99%